Literárněkulturalní ročenka „Tahy” v současné české literární kultuře - Studený, Jiří (Slavia Occidentalis, 2011)
The text provides a short survey of the original concept, the current structure and the contents of the literarycultural magazine “Tahy”, all in the context of the Czech literary science tendencies of the recent decade. It also contains a selection of the authors and regular contributors to the magazine, published by the team of the Department of Literary Culture and Slavistics at the Faculty of Arts of Pardubice University, together with Pavel Mervart Publishing House. One of he leading objectives of the magazine “Tahy” is to cover new trends in the contemporary Czech literary culture, both in scientific and artistic way, including some interesting student activities in the above-mentioned fields.